Regional variations in child health deprivation and its associated factors in Nigeria. - Victor Chima; Funmilola F Oyinlola; Joseph A Kupoluyi; Segun Tekun; Ifeyinwa U Anyanyo (PLOS Global Public Health)
Child health deprivations differ by socio-cultural differences and some demographic and socio-economic factors. Deprivation may be more pronounced by the geo-political zones/regions in Nigeria given the differences in their socio-cultural, education, religion, and economic particularly between the North and the South geo-political zones. Thus, this study examined regional variations in child health deprivation and its associated factors in Nigeria. The 2021 Nigeria Multiple Indicator Cluster Survey (MICS) was used for the study. A weighted sample size of 26,639 under-five children was analysed using STATA SE Version 14. Data were analysed using different descriptive statistics to examine regional variations in child health deprivation. Pearson's Chi-square and Binary logistic regression were performed to determine associated factors influencing child health deprivation in Nigeria at p < 0.05 level of significance. Results showed that nearly all children (96%) experience at least a deprivation in healthcare with a slight variation across regions in Nigeria. Child health deprivation was higher in the Northern regions than in the Southern regions. Interestingly, when compared to those who were not deprived, the Southwest region had the highest percentage of children who were not deprived (5%). The study also found lower odds of child health deprivation between children aged four (4) (OR = 0.65, 95%CI [0.50-0.85], p < 0.05), whose household head had tertiary education (OR = 0.19, 95%CI [0.13-0.28], p < 0.05), and from richest wealth index (OR = 0.06, 95%CI [0.04-0.10], p < 0.05). The study concludes that health deprivation is high among children in Nigeria irrespective of region of residence. Household and other factors have effects on the deprivation of healthcare for children according to the region of residence. This accentuates the need for a comprehensive review of policies and strategies related to health insurance schemes, and vaccination programs targeting under-five children in Nigeria.